THE EFFECT OF ORGANIZATIONAL CLIMATE, FATIGUE, STRESS AND MOTIVATION ON THE PERFORMANCE OF LECTURERS IN STIE WIDYA GAMA LUMAJANG. - Istichomah Istichomah; Imam Suroso; Muhaimin Dimyati (STIE Mandala Jember, 2018)
This study aimed to test the influence of organizational climate, fatigue, stress and motivation on the performance of lecturers in STIE Widya Gama Lumajang. Likewise to know which variable between organizational climate, job burnout, stress and motivation that has dominant influence on the performance of STIE Widya Gama Lecturer in Lumajang. So, it can be used as reference materials for research in the field of human resource management, especially for improving the performance of lecturers. Based on the analysis of each variable has fulfilled a standard rate of 5% significance. Therefore, the results also showed the Organization Climate should be developed so that the leader is able to provide a conducive climate of organizational effectiveness communication policy level and the level of participation of lecturer has been good. As for variable of motivation identifies the average lecturer’s needs provided by STIE Widya Gama Lumajang is still less for daily needs while the performance of lecturers have not been able to utilize the time as well as if there is a time that is loose and loose so that the utilization of time in work cannot be used maximally. And what needs to be noted is that the issue of devotion to society needs to be clearly defined and well organized.